AUTOTHERMAL REFORMING OF OF METHANE TO HYDROGEN PRODUCTION OVER Ni/Al2O3, Co/Al2O3 AND NiO-Co/MgO - T. D. Kusworo; A. R. Songip; N. A. S. Amir (Dept. of Chemical Engineering, Diponegoro University, 2004)
Autotherman reforming of methane to hydrogen gas was examined over Co/Al2O3, Ni/Al2O3 and NiO CoO/MgO catalyst. Among the catalyst examined NiO-CoO/MgO catalysts with 24 % metal loading exhibits not only the highest catalyst and selectivity but also remarkable stability. In addition the catalysts ware characterized by nitrogen adsorption (NA) , TPR, and XRD. The catalyst charecteristics is strongly influenced by interaction between support and metal exist. The excellent performance of NiO-CO/MgO resulted from the formation of an ideal solution between NiO, CoO and MgO Keywords : Autothermal reforming of methane, hydrogen production